KOLOKASI BERKONTRUKSI â€œNOMINA + VERBAâ€ DALAM BAHASA JEPANG PADA MINNA NO NIHONGO SHOKYUU DAN NIHONGO CHUUKYUU - Khoiriyah, Amalia Rizqi (Universitas Negeri Surabaya, 2018)
This research is motivated by the existence of problems in language, because each language has their own habits to join the words with certain words. This habit is called collocation. The focuss in this study, is the use of collocation with the construction of